Dectin-1 Compromises Innate Responses and Host Resistance against Neospora caninum Infection - Silva, Murilo Vieira da; Ferreira França, Flávia Batista; Mota, Caroline Martins; Macedo Júnior, Arlindo Gomes de; Ramos, Eliézer Lucas Pires; Santiago, Fernanda Maria; Mineo, José Roberto; Mineo, Tiago Wilson Patriarca (Frontiers in Immunology, 2017)
Neospora caninum is an intracellular protozoan parasite that has drawn increasing interest due to its association with worldwide repetitive bovine abortions, which cause billionaire losses to the meat and dairy industries annually. Innate immunity plays an important role in infection control, and N. caninum activates the production of inflammatory mediators through Toll-like Receptors (TLR), Nod-Like Receptors (NLR) and Mitogen Activated Protein Kinase (MAPK) signaling pathways. Advances in the knowledge of initial host-parasite interactions are desirable for the design of control measures against the infection, obliterating its pathogenesis. In that sense, we here aimed to describe the role of the innate C-type lectin receptor (CLR) Dectin-1 during the infection by N. caninum. With that intent, we observed that the absence of Dectin-1, observed in genetically depleted (Dectin-1-/-) mice or competitively inhibited by an inert agonist (Laminarin, LAM), rescued 50% of the mice infected with lethal doses of N. caninum. Dectin-1-/- and LAM-treated mice also presented a reduction in the parasite load during acute and chronic phases, associated to decreased inflammatory scores in the central nervous system. Amongst all the cell phenotypes that migrated to the initial site of infection, dendritic cells and macrophages gained subpopulations with high Dectin-1 surface expression. The impairment of the receptor in these cells led to a decreased parasite burden, as well as augmented production of IL-12p40. We also found that Dectin-1+ cells produced less reactive oxygen species (ROS) at the initial site of the infection, while mice deficient in NAPDH oxidase isoform 2 (NOX2-/-) were not able to control parasite replication and produce IL-12p40, even upon LAM treatment. Interestingly, the absence of functional Dectin-1 did not alter the susceptibility of mice against closely related T. gondii. In conclusion, the gathered data suggests that Dectin-1 is involved in the parasite-induced downmodulation of ROS and other key molecules triggered for the control of N. caninum infection, and is a promising target for future development of protocols intended for intervention against neosporosis.